2018
DOI: 10.1101/406454
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Harnessing Avidity: Quantifying Entropic and Energetic Effects of Linker Length and Rigidity Required for Multivalent Binding of Antibodies to HIV-1 Spikes

Abstract: Due to the low density of envelope (Env) spikes on the surface of HIV-1, neutralizing IgG antibodies rarely bind bivalently using both antigen-binding arms (Fabs) to crosslink between spikes (inter-spike crosslinking), instead resorting to weaker monovalent binding that is more sensitive to Env mutations. Synthetic antibodies designed to bivalently bind a single Env trimer (intra-spike crosslinking) were previously shown to exhibit increased neutralization potencies. In initial work, diFabs joined by varying l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…comparing the IC 50 s of the A/Wisconsin/67/05 and B/Harbin/7/94 strains of the 4-fused domains on an IgG backbone in Fig 5D to the corresponding IC 50 s for the individual antibody domains in Panels A and B). For such constructs, the composition of the linker can heavily influence the ability to multivalently bind and neutralize a virus [11,14], although Laursen et al surprisingly found little variation when they modified the length of their amino acid linker (see Table S11 in Ref [7]). Another curious feature of their system was that placing their linear 4-domain antibody (Fig 5C) on an IgG backbone (Fig 5D ) only resulted in a 2x decrease in IC 50 , suggesting that the two "arms" of the IgG could not simultaneously bind.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…comparing the IC 50 s of the A/Wisconsin/67/05 and B/Harbin/7/94 strains of the 4-fused domains on an IgG backbone in Fig 5D to the corresponding IC 50 s for the individual antibody domains in Panels A and B). For such constructs, the composition of the linker can heavily influence the ability to multivalently bind and neutralize a virus [11,14], although Laursen et al surprisingly found little variation when they modified the length of their amino acid linker (see Table S11 in Ref [7]). Another curious feature of their system was that placing their linear 4-domain antibody (Fig 5C) on an IgG backbone (Fig 5D ) only resulted in a 2x decrease in IC 50 , suggesting that the two "arms" of the IgG could not simultaneously bind.…”
Section: Discussionmentioning
confidence: 99%
“…Relative to the unbound HA state, the Ab A1 or Ab A2 portions of the antibody will neutralize the virus with relative probability c IC50,A1 or c IC50,A2 , respectively. Although neutralization is mediated by antibody binding, the two quantities may or may not be proportional [9][10][11], and hence we replace dissociation constants with IC 50 s in our model (see S1 Text Section C).…”
Section: Multidomain Antibodies Boost Breadth and Potency Via Aviditymentioning
confidence: 99%
See 2 more Smart Citations